PENGETAHUAN DAN KESIAPSIAGAAN MASYARAKAT MISKIN DALAM MENGHADAPI BANJIR ROB DI KECAMATAN PENJARINGAN JAKARTA UTARA - Widarjoto, Prasetyo; Budiarto, Arief; Triutomo, Sugeng (Jurnal Manajemen Bencana (JMB), 2019)
Climate change has resulted in rising sea levels that could lead to floods in coastal areas. This has an impact on the people living in the area. Factors affecting the vulnerability of communities in the face of disasters include poverty, education level, knowledge, awareness, and availability of easily accessible information. Poor socially vulnerable societies and living in coastal areas make it even more vulnerable to frequent robust flood threats. For that the poor must have knowledge and preparedness in the face of rob flood in its territory. This research is a qualitative research with case study approach aimed at analyzing the knowledge of the poor about rob flood and poor people's preparedness in the face of rob flood. The research location is located in Kecamatan Penjaringan, North Jakarta with the participants selected through purposive sampling technique. Techniques of collecting data using interviews, observations, and study documents that are then analyzed thematically according to the code that has been determined. The results show that poor people's knowledge about rob floods is still low as their knowledge has not yet led to the safety (safe culture) habit of dealing with robot floods, their knowledge is based solely on experience during their stay in areas affected by rob floods and often experience them, as well as poor people's preparedness in the face of floods, rob is still low, the poor have not been empowered or involved in programs or activities related to disaster preparedness. The poor need to improve their knowledge capacity through education, training, socialization, and simulations that can be done alone or with government support.